Prognostic Value of Platelet-Lymphocyte Ratio and High-Density Lipoprotein in Patients with Acute Myocardial Infarct - Lestari Lestari; Sulina Yanti Wibawa; Amaliyah Tahir Lopa; Darmawaty Rauf (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Acute Myocardial Infarct (AMI) is the main reason for mortality. Platelet to Lymphocyte Ratio (PLR) describes thrombocyte aggregation and inflammation that is linked to cardiovascular disease. High-Density Lipoprotein (HDL) is antiatherogenic. This study aims to analyze the prognostic value of PLR and HDL in patients with AMI. This study was a retrospective observational study by obtaining laboratory results from complete blood count and lipid profiles from inpatients with AMI (STEMI and NSTEMI) medical records during Mei 2019–August 2020. Receiver Operating Characteristics (ROC) analysis was done to get the PLR and HDL cut-off. Prognostic value evaluation was based on sensitivity, specificity, positive and negative predictive value, and accuracy. Results obtained were from 302 subjects with a mean age of 58.4+9.6 years old, with most male patients (74.5%). Receiver operating characteristics curve analysis showed an 0.514 Area Under Curve (AUC) for PLR with p=0.685. High-density lipoprotein ROC was 0.573 with a p=0.033 (p< 0.05), with HDL cut-off = 50.0; sensitivity 72.7%, specificity 32.3%, positive predictive value 63.3%, negative predictive value 42.0% and 57.3% accuracy.Platelet to lymphocyte ratio mean was lower in the HDL <50 group (187.9) compared to the HDL > 50 (210.8), (p=0.009). High-density lipoprotein can be concluded as a potential prognostic factor of acute myocardial infarct. The lower the HDL, the greater the risk for a poor prognosis. A big-scale prospective study should be held to clarify and confirm these findings.